1992
DOI: 10.1073/pnas.89.15.7144
|View full text |Cite
|
Sign up to set email alerts
|

At least five related, but distinct, hepatitis C viral genotypes exist.

Abstract: Hepatitis C virus, the major causative agent of blood-borne non-A, non-B hepatitis in the world, has been the subject of considerable nucleic acid sequence analysis. Although all reported hepatitis C sequences from the United States have been represented by the prototype hepatitis C virus type 1 sequence, two groups of variant sequences have been reported in Japan. However, we have noted five distinct, but related, genotypes (I-V) throughout the world, based on detailed sequence determination and analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
1
4

Year Published

1993
1993
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(144 citation statements)
references
References 26 publications
5
134
1
4
Order By: Relevance
“…When genotyping of these patients was performed we used the method of Cha et al 22 which allows the identification of four genotypes (1a,1b, 2 and 3), as previously mentioned. The lack of stocked serum prevented us from performing a second analysis with the method currently in use, which allows subtyping of genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When genotyping of these patients was performed we used the method of Cha et al 22 which allows the identification of four genotypes (1a,1b, 2 and 3), as previously mentioned. The lack of stocked serum prevented us from performing a second analysis with the method currently in use, which allows subtyping of genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The first 8 is based on the amplification of cDNA using two sets of primers specific for the 5â€ČUTR and for the E region of HCV genome and subsequent Southern blot hybridization, using four 32 P-labeled genotype-specific oligonucleotide probes. 22 This assay allows the identification of four genotypes, respectively, 1a, 1b, 2, 3, according to Simmonds classification 23 but is very laborious and does not allow the identification of some clinically relevant types and subtypes. Due to these limitations a second assay (2nd generation Line Probe Assay, LiPA; Innogenetics, Brussels, Belgium) was recently adopted.…”
Section: Serological Testsmentioning
confidence: 99%
“…(Simmonds et at., 1993;Simmonds, 1995). Up to the present, at least 34 genotypes in nine genetic groups have been reported (Cha et al, 1992;Mori et al, 1992;Bukh et al, 1993Bukh et al, , 1994Simmonds et al, 1993;Stuyver et al, 1993Stuyver et al, , 1994Okamoto et al, 1994;Tokita et al, 1994aTokita et al, , b, 1995. HCV genotypes have distinct geographical distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide sequence analyses of HCV clones isolated in different places in the world revealed that there are significant sequence diversities (8)(9)(10)(11)(12)(13)(14)(15). The analysis of the region of non-structure 5 (NS5) of the HCV genome found, at least five different HCV genotypes in the world (16). To understand the HCV genotypes existing in Taiwan, we employed the method of reverse transcription-polymerase chain reaction in the NS5 region of HCV isolated from hemodialysis patients (antibody against HCV core antigen, OD >2).…”
Section: Introductionmentioning
confidence: 99%
“…Cha's classification (16) suggested that two genotypes of HCV were found in these serum samples; type 11 (2/18.2%) and type III (9/81.8%). Our study indicates also that NS5 is an adequate target region to differentiate HCV strains derived from different patients in the same hospital.…”
mentioning
confidence: 99%